2020
DOI: 10.4038/sljid.v10i1.8270
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris: A brief review

Abstract: This an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These findings are like this study because, during the study period, C. tropicalis and C. parapsilosis were most prominent. A recent study conducted by Sigera et al, 2019 in Sri Lanka has also demonstrated that non albicans species are more prominent than C. albicans in Sri Lanka. Their finding on C. tropicalis and C. parapsilosis being the most prominent species agrees with the findings of this study.…”
Section: Discussionmentioning
confidence: 91%
“…These findings are like this study because, during the study period, C. tropicalis and C. parapsilosis were most prominent. A recent study conducted by Sigera et al, 2019 in Sri Lanka has also demonstrated that non albicans species are more prominent than C. albicans in Sri Lanka. Their finding on C. tropicalis and C. parapsilosis being the most prominent species agrees with the findings of this study.…”
Section: Discussionmentioning
confidence: 91%